Clinical Profile of Non-Motor Symptoms in Patients with Essential Tremor: Impact on Quality of Life and Age-Related Differences - Shalash, Ali S. (Tremor Other Hyperkinet Mov (N Y), 2019)
BACKGROUND: Identifying the clinical phenotypes of non-motor symptoms (NMSs) of essential tremor (ET) among different populations is necessary due to their impact on the quality of life (QoL). This study aimed to investigate the clinical phenotype and impact of NMSs on QoL in Egyptian patients with ET. METHODS: Thirty ET patients were compared to 30 matched controls. Subjects were evaluated by the Fahn-Tolosa-Marin Tremor Rating Scale, Non-Motor Symptoms Scale (NMSS), Montreal Cognitive Assessment, Hamilton Anxiety Rating Scale, Beck Depression Inventory, Pittsburgh Sleep quality Index, and the Short Form 36 Health Survey Questionnaire. Both groups were divided into two subgroups of younger (<45 years, 14 patients) and older age (>45 years, 16 patients) groups, to investigate age-related differences. RESULTS: ET patients showed significantly worse cognition, depression, anxiety, sleep and NMSS domains (p < 0.001), compared to controls, that negatively affected and predicted QoL. Older patients had more cognitive impairment (p = 0.003) and worse sleep/fatigue (p = 0.032) and sexual functions (p = 0.006), compared to younger group. DISCUSSION: The study supports that NMSs are integral part of ET, negatively affect QoL, and similarly affect younger and older patients. Therefore, NMSs should be explored for proper care of ET patients.